Evaluation of a pixelated large format CMOS sensor for x‐ray microbeam radiotherapy. Issue 3 (6th January 2020) - Flynn, Samuel; Price, Tony; Allport, Philip P.; Silvestre Patallo, Ileana; Thomas, Russell; Subiel, Anna; Bartzsch, Stefan; Treibel, Franziska; Ahmed, Mabroor; Jacobs‐Headspith, Jon; Edwards, Tim; Jones, Isaac; et al.
Abstract : Purpose: Current techniques and procedures for dosimetry in microbeams typically rely on radiochromic film or small volume ionization chambers for validation and quality assurance in 2D and 1D, respectively. Whilst well characterized for clinical and preclinical radiotherapy, these methods are noninstantaneous and do not provide real time profile information. The objective of this work is to determine the suitability of the newly developed vM1212 detector, a pixelated CMOS (complementary metal‐oxide‐semiconductor) imaging sensor, for in situ and in vivo verification of x‐ray microbeams. Methods: Experiments were carried out on the vM1212 detector using a 220 kVp small animal radiation research platform (SARRP) at the Helmholtz Centre Munich. A 3 x 3 cm 2 square piece of EBT3 film was placed on top of a marked nonfibrous card overlaying the sensitive silicon of the sensor. One centimeter of water equivalent bolus material was placed on top of the film for build‐up. The response of the detector was compared to an Epson Expression 10000XL flatbed scanner using FilmQA Pro with triple channel dosimetry. This was also compared to a separate exposure using 450 µm of silicon as a surrogate for the detector and a Zeiss Axio Imager 2 microscope using an optical microscopy method of dosimetry. Microbeam collimator slits with range of nominal widths of 25, 50, 75, and 100 µm were used to compare beam profiles and determine sensitivity of the detector and both film measurements to different microbeams. Results: The detector was able to measure peak and valley profiles in real‐time, a significant reduction from the 24 hr self‐development required by the EBT3 film. Observed full width at half maximum (FWHM) values were larger than the nominal slit widths, ranging from 130 to 190 µm due to divergence. Agreement between the methods was found for peak‐to‐valley dose ratio (PVDR), peak to peak separation and FWHM, but a difference in relative intensity of the microbeams was observed between the detectors. Conclusions: The investigation demonstrated that pixelated CMOS sensors could be applied to microbeam radiotherapy for real‐time dosimetry in the future, however the relatively large pixel pitch of the vM1212 detector limit the immediate application of the results.